INTERDISCIPLINARITY IN SECONDARY EDUCATION AND PHILOSOPHY TEACHING - Fernandes, Mateus de Melo; Fernandes, Marcela de Melo (Seven Editora, 2025)
Interdisciplinarity in philosophy teaching has gained prominence as an essential pedagogical approach for promoting critical and integral education. Interdisciplinary teaching is one of the possibilities that can provide productivity and is suited to contemporary educational needs. The aim of this article was to conceptualize interdisciplinarity and analyse it within the school context, especially in secondary education. The methodology applied was documentary analysis, with a bibliographic survey of scientific articles, present in the thesis bank of the Coordination for the Improvement of Higher Education Personnel (Capes), in the Scientific Electronic Library Online (SciELO), literature that deals with the theme and in annals of scientific events in education, based on the study by Fazenda (2024); Lück (2013); Ramos; Freitas and Pierson (2013) and the BNCC. Finally, it can be concluded that interdisciplinary work in secondary education and philosophy teaching, when carried out clearly and coherently, effectively provides an integral education for students. DOI: https://doi.org/10.56238/sevened2024.037-149